Association between the atherogenic index of plasma and new-onset non-alcoholic fatty liver disease in non-obese participants - Li, Kemin; Li, Ji; Cheng, Xiaoyun; Wang, Jing; Li, Jingnan (Frontiers in Endocrinology, 2022)
Introduction: Non-alcoholic fatty liver disease (NAFLD) in the non-obese population accounts for a large proportion of NAFLD. Atherogenic index of plasma (AIP, defined as the logarithm of the triglyceride/high-density lipoprotein cholesterol ratio.) can provide a stronger reflection of dyslipidemia and studies on the longitudinal association between AIP and NAFLD were limited in non-obese participants, especially in different BMI groups. Methods: We performed a post-hoc analysis of data obtained from the Dryad data repository (Dryad is a nonprofit open database of medicine.) and explored the predictive value of AIP on the risk of NAFLD among non-obese participants. Results: This study included 16173 participants with AIP, of which 2322(14.4%) non-obese participants developed into individuals with NAFLD with the 5-year follow-up examination. The difference between AIP quartiles in the cumulative estimation of new-onset NAFLD was significant, and with increased AIP, the cumulative new-onset NAFLD gradually increased. Participants in higher AIP quartiles had a significantly increased risk of NAFLD. In the fully adjusted model 3, hazard ratios of the new-onset NAFLD for subjects in Q2, Q3, and Q4 of AIP were 2.00 (1.59, 2.53), 2.61 (2.09, 3.72), and 4.49 (3.62, 5.57) respectively. Meanwhile, the trend test for the association between AIP quartiles and the new-onset NAFLD presented that AIP quartile was positively and strongly associated with the new-onset NAFLD (adjusted hazard ratio (95%CI) in Model 3: 1.59 (1.51, 1.67), P<0.001). We found that AIP was also positively and strongly associated with new-onset NAFLD in different sex groups and different age groups in female patients. Moreover, the predictive ability of AIP was no significant difference in different sex groups and different age groups in female patients. In the subgroup analysis, we found that in the low BMI population, the predictive effect of AIP for new-onset NAFLD was expanded by 2-3 times for each quality increase of AIP. Conclusion: This study found that AIP was a strong independent risk factor for new-onset NAFLD among non-obese individuals especially in the low BMI participants, and screening for AIP in this population can be used to prevent future NAFLD.